PENENTUAN PRIORITAS SUPPLIER TEPUNG TERIGU MENGGUNAKAN METODE FUZZY ANALYTICAL HIERARCHY PROCESS (F-AHP) DI CV XYZ - Putri, Suci Ario Kusuma; Adianto, R. Hari (e-Proceeding FTI, 2024)
CV XYZ is one of the famous brownie cake shops in the city of Bandung. The most important raw material in the manufacture of brownies is flour. CV XYZ has 7 flour suppliers. However, from these suppliers, CV XYZ has not yet determined the supplier selection criteria. Supplier selection can be said to be an important issue, because it is an important point in the success of a product from the company, you also have to be selective in choosing it. Especially with problems from existing suppliers, including inadequate procurement of wheat flour, ordinary or poor flour quality, high-priced flour, and delays in delivery, which is a problem for the company in determining suppliers. This complicated selection of suppliers is a reference for using the Fuzzy Analytical Hierarchy Process (FAHP) method in order to obtain the best supplier for the company by considering the criteria in the selection and priority order of suppliers. The data needed for this study are preliminary questionnaires and pairwise comparison questionnaires which are distributed to the respondents concerned in making supplier selection decisions. There are five supplier selection criteria used, namely quality, price, delivery, warranty and claims policies, and communication systems. The sub criteria used are fourteen sub criteria. Based on the research results, the sequence of flour suppliers was obtained, namely CV XYZ, CV XYZ, CV XYZ, PT XYZ, PT XYZ, XYZ, and XYZ. Keywords: Supplier Selection; Criteria; AHP; Fuzzy Analytical Hierarchy Process (FAHP) CV XYZ adalah salah satu toko kue brownies yang terkenal di Kota Bandung. Bahan baku yang paling utama dalam pembuatan brownies yaitu tepung terigu. CV XYZ memiliki 7 supplier tepung terigu. Namun dari supplier-supplier tersebut, CV XYZ belum menentukan kriteria pemilihan supplier. Pemilihan supplier dapat dikatakan sebagai permasalahan yang penting, karena menjadi poin penting dalam keberhasilan suatu produk dari perusahaan tersebut, juga harus selektif dalam memilihnya. Apalagi dengan permasalahan dari supplier yang ada antara lain pengadaan tepung terigu yang kurang, tingkat kualitas tepung yang biasa atau buruk, tepung dengan harga yang mahal, dan keterlambatan pengiriman menjadi masalah perusahaan dalam menentukan supplier. Pemilihan supplier yang rumit ini menjadi acuan untuk menggunakan metode Fuzzy Analytical Hierarchy Process (FAHP) agar memperoleh supplier yang terbaik untuk perusahaan dengan mempertimbangkan kriteria dalam pemilihan dan urutan prioritas supplier. Data yang dibutuhkan untuk penelitian ini adalah kuesioner pendahuluan dan kuesioner perbandingan berpasangan yang disebarkan kepada responden yang bersangkutan dalam pengambilan keputusan pemilihan supplier. Kriteria pemilihan supplier yang digunakan berjumlah lima yaitu kriteria kualitas, harga, pengiriman, jaminan dan kebijakan klaim, dan sistem komunikasi. Sub kriteria yang digunakan berjumlah empat belas sub kriteria. Berdasarkan hasil penelitian diperoleh urutan supplier tepung terigu yaitu CV XYZ, CV XYZ, CV XYZ, PT XYZ, PT XYZ, XYZ, dan XYZ. Kata kunci: Pemilihan Supplier; Kriteria; AHP; Fuzzy Analytical Hierarchy Process (FAHP).